2011
DOI: 10.1074/jbc.m111.238394
|View full text |Cite
|
Sign up to set email alerts
|

Role of Novel Dimeric Photosystem II (PSII)-Psb27 Protein Complex in PSII Repair

Abstract: The multisubunit membrane protein complex Photosystem II (PSII) catalyzes one of the key reactions in photosynthesis: the light-driven oxidation of water. Here, we focus on the role of the Psb27 assembly factor, which is involved in biogenesis and repair after light-induced damage of the complex. We show that Psb27 is essential for the survival of cyanobacterial cells grown under stress conditions. The combination of cold stress (30°C) and high light stress (1000 mol of photons ؋ m ؊2 ؋ s ؊1 ) led to complete … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
54
0
3

Year Published

2011
2011
2017
2017

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 46 publications
(66 citation statements)
references
References 43 publications
9
54
0
3
Order By: Relevance
“…By contrast, no detectable CyanoQ bound to the cobalt resin when a non-tagged WT sample was tested. As expected, the D1 and PsbO subunits of PSII co-purified with His-tagged CP43, as did significant amounts of Psb27, which is known to be a component of non-oxygen-evolving PSII complexes (Nowaczyk et al 2006; Grasse et al 2011). In contrast only trace amounts of CyanoP co-purified with CP47-His under the experimental conditions used.
Fig.
…”
Section: Resultssupporting
confidence: 64%
“…By contrast, no detectable CyanoQ bound to the cobalt resin when a non-tagged WT sample was tested. As expected, the D1 and PsbO subunits of PSII co-purified with His-tagged CP43, as did significant amounts of Psb27, which is known to be a component of non-oxygen-evolving PSII complexes (Nowaczyk et al 2006; Grasse et al 2011). In contrast only trace amounts of CyanoP co-purified with CP47-His under the experimental conditions used.
Fig.
…”
Section: Resultssupporting
confidence: 64%
“…This was subsequently confirmed in a later study in the thermophilic cyanobacterium Thermosynechococcus elongatus, which revealed that Psb27 is a lipoprotein associated with a monomeric PSII complex lacking the PsbO, PsbV, and PsbU extrinsic proteins (Nowaczyk et al, 2006) and also lacking a functional Mn 4 Ca cluster (Mamedov et al, 2007). Dimeric PSII-Psb27 complexes, inactive for water splitting, can also be isolated from T. elongatus grown at low temperature (Grasse et al, 2011).…”
mentioning
confidence: 53%
“…PCC 6803 [177]. Grasse et al demonstrated that the Psb27 assembly factor is essential for the survival of cyanobacterial cells grown under stress conditions [178]. Wu et al also confirmed that D1 protein turnover is involved in the protection of PSII from UV-B-induced damage in the cyanobacterium Arthrospira (Spirulina) platensis [47].…”
Section: Repair and Resynthesis Of Damaged Dna And Proteins In Cyanobmentioning
confidence: 91%